The business model through an ecosystem perspective: An exploratory approach applied to a cultural card - Bernardo, B.; Ferreira, P. A. (International Conference “Keep it Simple, Make it Fast! DIY cultures and global challenges” (KISMIF Conference 2021), 2021)
This paper aims to explore the relationship between the concepts of business model and ecosystem, applied to the creation of cultural cards that generate symbolic, cultural, social and economic value. This is a hybrid study - conceptual and empirical - and exploratory, based on literature review and data analysis collected by 602 questionnaires and 27 interviews. Was conducted a mixed methodology, qualitative and quantitative, and an interpretivist paradigm of constructivist nature. Three main conclusions were drawn. The first suggests that a cultural card is only viable if designed and managed as a business model, with all blocks coherent and articulated with each other and executed in synchronization. The second configures a cultural card as a complex network of interdependent actors functioning in an ecosystem logic that enhances economic growth affirmed by creative competitiveness. The third points out a cultural card as a cultural agent, for the symbolic value it promotes dominated by the discourse of ‘now’ and ‘already’, inherent in the access-based economy This paper: (1) perspectives that cultural and creative development involves the creation of a valuable macro ecosystem and a robust national network articulated with local and specific micro ecosystems; (2) evidences the importance of creativity and innovation, inherent to the business model, for the production and diffusion of knowledge, fruition and democratization of culture in the face of the diversity of emerging market segments and (3) provides propositions applicable to the universe of cultural and creative industries that are carriers of new insights that can be explored and knowledge increased. The value of this paper lies in the exploration of a new look at the theme of cultural cards embodied in a logic of an ecosystemic business model.